Stability of smooth soHtary waves for the generahzed Korteweg - de Vries equation with combmed dispersion - Yin, J. L. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
The orbital stability problem of the smooth solitary waves in the generalized Korteweg - de Vries equation with combined dispersion is considered. The results show that the smooth solitary waves are stable for an arbitrary speed of wave propagation.